2023
DOI: 10.3389/fonc.2022.1074675
|View full text |Cite
|
Sign up to set email alerts
|

Definitive intensity modulated proton re-irradiation for lung cancer in the immunotherapy era

Abstract: IntroductionAs immunotherapy has improved distant metastasis-free survival (DMFS) in Non-Small Cell Lung Cancer (NSCLC), isolated locoregional recurrences have increased. However, management of locoregional recurrences can be challenging. We report our institutional experience with definitive intent re-irradiation using Intensity Modulated Proton Therapy (IMPT).MethodRetrospective cohort study of recurrent or second primary NSCLC or LS-SCLC treated with IMPT. Kaplan-Meier method and log-rank test were used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Reirradiation with FLASH PRT after an initial scheme of Standard PRT is shown to mitigate RTinduced dermatitis, fibrosis, lymphedema, and bone damage. These acute and late toxicities are observed in the clinical setting after proton reirradiation, including in the treatment of sarcomas 27 , abdominal tumors 19,[28][29][30] , head and neck tumors 15,31 , esophageal cancer 17 , breast cancer 4,32 , and lung cancer 14,33,34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reirradiation with FLASH PRT after an initial scheme of Standard PRT is shown to mitigate RTinduced dermatitis, fibrosis, lymphedema, and bone damage. These acute and late toxicities are observed in the clinical setting after proton reirradiation, including in the treatment of sarcomas 27 , abdominal tumors 19,[28][29][30] , head and neck tumors 15,31 , esophageal cancer 17 , breast cancer 4,32 , and lung cancer 14,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the cumulative dose that is delivered to the region is important because the initial dose that was delivered will contribute to the probability of an adverse toxicity. Modern techniques such as intensity-modulated radiation therapy (IMRT) and stereotactic body radiotherapy (SBRT) can provide better conformality to the tumor volume than standard photon delivery and have been used to minimize the associated morbidities of reirradiation [6][7][8][9][10][11][12][13][14] . Proton radiotherapy (RT) is also used in reirradiation because of its physical characteristics, as protons deposit most of their energy within a narrow range (Bragg peak) with little exit dose.…”
Section: Introductionmentioning
confidence: 99%
“…A phase II, single-arm trial (NCT03087760) of consolidation pembrolizumab after PRT reirradiation for locoregional recurrences in 22 patients with NSCLC conducted between 2017 and 2021 showed acceptable PFS and favorable OS, with late grade 5 toxicity occurring in only 2 patients 18. A retrospective cohort study of patients with recurrent NSCLC treated with definitive IMPT re-irradiation between 2019 and 2021 showed prolonged disease control with limited toxicity, particularly in combination with immunotherapy 19. A phase II clinical study of 31 HNSCC patients enrolled between March 2018 and July 2020 showed the combination of durvalumab/tremelimuab and PRT was tolerated well in individuals who had undergone extensive prior treatments 20.…”
mentioning
confidence: 99%